Stress Levels, Macronutrient Intake, and Physical Activity and Their Relation to Nutritional Status in New Students - Novera Herdiani (Universitas Nahdlatul Ulama Surabaya, 2026)
New students are prone to lifestyle changes, such as increased stress, changes in diet, and decreased physical activity, which can affect their nutritional status. Nutritional problems can affect the health and academic achievement of the students. This study aimed to examine the correlation of the nutritional status of new students with the stress levels, macronutrient intake, and physical activity. With a cross-sectional design, this study is an analytical observational study. The population consisted of all 263 new students at the Faculty of Health. The sample consisted of 73 students, selected using proportional stratified random sampling. Stress level was measured using the DASS-21 questionnaire, nutrient intake through a 24-hour food recall, physical activity using the IPAQ-SF, and nutritional status through measurement of Body Mass Index. Data were analysed using the Spearman correlation test. The results showed severe stress (28.8%), normal carbohydrate intake (27.4%), moderate protein deficit (34.2%), mild fat deficit (35.6%), moderate activity (53.4%), and normal nutritional status (60.3%). This study found a relationship between stress level and nutritional status (p=0.002, r=-349), macronutrient intake (carbohydrate, protein, fat) with nutritional status respectively (p=0.007, r=0.315), (p=0.000, r=0.595), (p=0.000, r=0.481), and physical activity has a relationship with nutritional status (p=0.005, r=-0.323). In conclusion, there is a relationship between stress levels, macronutrient intake, and physical activity with nutritional status. The strongest relationship to nutritional status is macronutrient intake, especially protein and fat. It is expected that new students possess good stress management skills, a balanced nutritional intake, and engage in sufficient physical activity. Keywords: Nutrients, Nutritional Status, Physical Activity, Stress